Biogeochemical sediment core data (LVC18-S1, LVC18-S2, LVC18-S3 and LVC18-S4) from Lake Victoria, Eastern Africa - Giulia Wienhues; Andrea Lami; Stefano M Bernasconi; Hendrik Vogel; Martin Grosjean (PANGAEA, 2025)
This dataset presents multi-proxy records from four sediment cores (LV1-LV4) collected in Lake Victoria, spanning the past 17 kyr. Core sites range from 13.4 to 63 m water depth, capturing spatial and environmental variability in the past. The dataset integrates non-desctructive analyses X-ray fluorescence (XRF), hyperspectral imaging (HSI) with biogeochemical data (e.g., TOC, TN, bSi, δ13C, δ15N, sedimentary pigments).